PENERAPAN ARSITEKTUR JENGKI PADA PERANCANGAN HOTEL RESORT DI KAWASAN WISATA ALAM JATINEGARA, TEGAL - Kurnia Nur Prita Sari; Putri Suryandari (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
The Jengki architecture as the original style of the Indonesian architectural style and has been forgotten as the ages evolved, was applied in the design of a five star class (*****) Resort Hotel in the Jatinegara Nature Tourism Area, Tegal. The number of tourist areas developed in Jatinegara Subdistrict has increased the number of local and non-local visitors who need accommodation facilities. The increasing number of tourists was also targeted to reintroduce Jengki Architecture.